Un trípode de tipo chipriota procedente de la Clota (Calaceite, Teruel) - Rafel Fontanals, Núria (Complutum, 2002)
Bronze Tripod in Cypriot Style coming from La Clota (Calaceite, Teruel). The aim of this brief essay is to present two little fragments of bronze coming from a tomb in La Clota (Calaceite, Teruel) whi h were recently identified as being a part of a tripod in cypriot style. We examine in brief the main questions raised y the find: chronology, origins, social context and influence on local craftsmanship.